2014
DOI: 10.2147/ott.s67812
|View full text |Cite
|
Sign up to set email alerts
|

A survival analysis comparing women with ovarian low-grade serous carcinoma to those with high-grade histology

Abstract: Ovarian low-grade serous carcinoma (LGSC) and high-grade serous carcinoma have distinct molecular profiles, clinical behaviors, and treatment responses. The survival advantage for patients with low-grade carcinoma compared with patients with high-grade histology remains controversial. We retrospectively reviewed the medical charts of 381 patients with ovarian serous carcinoma at Peking Union Medical College Hospital from 2007 to 2010. Patients were classified into two groups according to MD Anderson two-tier s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 35 publications
1
22
2
2
Order By: Relevance
“…Most patients diagnosed with OC, survival is theorized to be 100%, who are still alive after 5-years, are presumably living with the disease rather than living disease-free. 5 Our analysis demonstrated that the DFS was 18.3 months (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). The Surveillance, Epidemiology and End Results-SEER database from 1995 to 2007 with epithelial OC who were actively followed-up and age 20 years or older were included for analyzing OS in the United States (40.692 patients) and OS was 65%, 44%, and 36% at 2, 5, and 10 years, respectively.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Most patients diagnosed with OC, survival is theorized to be 100%, who are still alive after 5-years, are presumably living with the disease rather than living disease-free. 5 Our analysis demonstrated that the DFS was 18.3 months (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). The Surveillance, Epidemiology and End Results-SEER database from 1995 to 2007 with epithelial OC who were actively followed-up and age 20 years or older were included for analyzing OS in the United States (40.692 patients) and OS was 65%, 44%, and 36% at 2, 5, and 10 years, respectively.…”
Section: Discussionmentioning
confidence: 86%
“…Some studies reported that increasing age was most strongly associated with poor survival. 9,10,[18][19][20]22 However, in the other studies of Oge et al 7 and Buldanlı et al 11 revealed that age was not was not effected by the age of the patients in OC.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Currently, OSC is no longer considered to be a homogeneous disease worldwide. It is now recognized as a group of diseases that can be classified based on distinctive morphologic and molecular genetic features [8]. Conventionally, the origin of serous tumour is the ovarian surface epithelium or cortical inclusion cysts.…”
Section: Literature Reviewmentioning
confidence: 99%